Theory, practice, and design criteria for utilizing artificial reefs to increase production of marine fishes - Pondella, Daniel J.; Claisse, Jeremy T.; Williams, Chelsea M. (Frontiers in Marine Science, 2022)
Increasing the production of marine fishes is a tractable goal with wide socioeconomic and ecological appeal. Ecosystem restoration projects that increase the amount of suitable habitat in an area and/or habitat quality enhance both fishery production and ecosystem services. Fortuitously, there are a wealth of studies documenting the specific examples of restoring these services from successful artificial reef deployments. Considering the need to create future structures in a variety of scenarios and locations, it is salient to summarize the mechanisms through which increased secondary production occurs and the design considerations. To achieve this objective maximizing ecological processes including the provisioning of planktonic and epibenthic food resources and related trophic pathways, and those associated with life-stage specific habitat use (e.g., recruitment, juvenile survival, reproductive output) are critical mechanisms of productive reefs. We synthesized this information by addressing the structural and ecological theory of artificial reef design based upon physical attributes such as complexity, vertical relief, habitat heterogeneity, and spatial scale. Within this framework we summarized the mechanisms that may be used to increase secondary fish production and propose a general theory for optimization of these variables.